2018
DOI: 10.21303/2504-5695.2018.00681
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Influence of Antimicrobial Preparations on the Shelf Life of Broccoli Cabbage

Abstract: and vegetable and storage Kharkiv National Agricultural University named after V. V. Dokuchayev "Dokuchaevske -2", Kharkiv region, Ukraine, 62483 zim-hot@rambler.ru Ludmila Gaevaya Department of fruit and vegetable and storage Kharkiv National Agricultural University named after V. V. Dokuchayev "Dokuchaevske -2", Kharkiv region, AbstractStudies of the effect of antimicrobial agents on the conservation of broccoli cabbage have been conducted. The late hybrids of broccoli Ironman F1, Agassi F1, Beaumont F1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The microbial inactivation effects are mainly due to pH reduction, disturbance of membrane transport and/or permeability, anion accumulation, or reduction in internal cellular pH (Ramos et al, 2013). Acidification with citric acid was used to preserve fresh cut apples (DiPersio et al, 2003;Derrickson-Tharrington et al, 2005;Chen et al, 2016) and iceberg lettuce (Akbas & Olmez, 2007) while dipping in solutions of benzoic and sorbic acids was performed to increase the shelf life of broccoli florets (Irkin et al, 2015;Pusik et al, 2018). Citric and ascorbic acids have been used in fresh and fresh-cut fruits and vegetables to control browning (Li-Qin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The microbial inactivation effects are mainly due to pH reduction, disturbance of membrane transport and/or permeability, anion accumulation, or reduction in internal cellular pH (Ramos et al, 2013). Acidification with citric acid was used to preserve fresh cut apples (DiPersio et al, 2003;Derrickson-Tharrington et al, 2005;Chen et al, 2016) and iceberg lettuce (Akbas & Olmez, 2007) while dipping in solutions of benzoic and sorbic acids was performed to increase the shelf life of broccoli florets (Irkin et al, 2015;Pusik et al, 2018). Citric and ascorbic acids have been used in fresh and fresh-cut fruits and vegetables to control browning (Li-Qin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This reduced disease losses in 10 times and maintained the quality of fruits [24]. Immersion of peaches in water of 37 °C and their subsequent treatment with Cryptococcus laurentii reduced losses caused by blue mold and wet rot [25]. Sorbic acid and benzoic acids act against mold fungi and yeast and partly bacteria [4].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Citric and ascorbic acids are commonly used in fruit and vegetable washing (Velázquez et al, 2009;Ramos et al, 2013) while other acids, such as propionic, sorbic, and benzoic acids, have been used for many years as food and drink preservatives. Akbas and Olmez (2007) reported that lactic and citric acid dipping could be alternative treatments to chlorine dipping to prolong the shelf life of fresh-cut iceberg lettuce while Pusik et al (2018) found that treatment with 0.5% solution of citric acid, 0.2% benzoic acid, 0.05% sorbic acid increased the shelf life of broccoli. Jiang et al (2004) reported that 0.1 M citric acid extended the shelf life, inhibited surface coloration and disease development, and reduced the loss in eating quality of fresh-cut Chinese water chestnut while Pao and Petracek (1997) demonstrated that infusion of peeled oranges with citric acid solution (0.1, 0.25, 0.5, and 1.0% w/v) during the peeling process reduced the surface pH of peeled fruits and extended their shelf life due to the inhibition of spoilage bacteria.…”
Section: Introductionmentioning
confidence: 99%